2010
DOI: 10.1080/07399331003717298
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for the Right Time: How and Why Young Thai Women Manage to Avoid Heterosexual Intercourse

Abstract: Nineteen young Thai women were purposively selected from networks of nongovernmental organizations involving children and youths in Bangkok. Our grounded theory findings indicated that these young women used the basic social process they called "waiting for the right time" in order to maintain heterosexual abstinence. Waiting for the right time involved one overarching condition, honoring parental love, and included three overlapping properties: learning rules, planning life path, and ways of preserving virgin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(39 citation statements)
references
References 33 publications
(28 reference statements)
2
37
0
Order By: Relevance
“…Boys were more likely to engage in early sexual behaviors which is an expected finding and supported by earlier studies [15,17]. Thai girls may be less likely to be involved in early sexual activity due to gender norms that are still prevalent in Thailand, which favour females remaining virgins until marriage [27,47]. It is worth noting that while the prevalence of Early SI was higher for boys compared to girls, the average age of early SI was not significantly different indicating a trend for both genders to initiate sex at an earlier age.…”
Section: Discussionasupporting
confidence: 72%
“…Boys were more likely to engage in early sexual behaviors which is an expected finding and supported by earlier studies [15,17]. Thai girls may be less likely to be involved in early sexual activity due to gender norms that are still prevalent in Thailand, which favour females remaining virgins until marriage [27,47]. It is worth noting that while the prevalence of Early SI was higher for boys compared to girls, the average age of early SI was not significantly different indicating a trend for both genders to initiate sex at an earlier age.…”
Section: Discussionasupporting
confidence: 72%
“…The delay of first sexual intercourse in the current study may have been influenced by Thai traditional culture, in which early experience with sexual intercourse is considered socially unacceptable (Sridawruang et al, 2010;Supametaporn et al, 2010). Biologically, we found that early sexual activity after menarche (< 6 years) led to greater susceptibility to SCCA.…”
Section: Discussionmentioning
confidence: 58%
“…Given the double standard involving the girls' premarital sexual experience, Thai girls may choose to adopt a basic social process of 'waiting for the right time' to avoid premarital sex. The process consists of three components: learning proper rules, planning her life's sexual path, and preserving virginity by not giving in to sexual temptation (Supametaporn, Stern, Rodcumdee, & Chaiyawat, 2010). An attitude against premarital sex may be said to underlie this social process.…”
Section: Premarital Sex In Thailandmentioning
confidence: 99%